The Role Of Experience On Digital Payments Brand Loyalty Through Expectations As A Mediating Variable: English - Kapriani, Kapriani; Jusman, Ikhsan Amar; Hasniaty, Hasniaty (Economics and Digital Business Review, 2023)
This study aims to determine the effect of payment experience on brand loyalty of ShopeePay digital payments in Makassar City with expectations as a mediating variable. This research is quantitative, namely the sampling method using an accidental sampling technique with 100 respondents. The data analysis technique used in this research is multiple linear regression analysis. The results showed that experience and expectations significantly affected ShopeePay digital payments brand loyalty in Makassar City. Experience has a significant effect on expectations. Expectations mediate the relationship between experience and ShopeePay digital payments brand loyalty in Makassar City.